Pengenalan Pola Tulisan Tangan Untuk Mengetahui Kepribadian Seseorang Menggunakan Metode Jaringan Hamming - Jaenal Arifin; Eko Vidiantoro; Endang Setyati (Jurnal Ilmiah Teknologi Informasi Asia, 2012)
There are some ways how to identify humans’ personality, such as by image recognition, fingerprint, signature, handwriting patterns and so on. In analyzing human’s personality for example as in employee recruitment, an experts who understand this field extremely required. Then, the problem will appear when the expert is not in place, thus the development of technology hopefully can solve this problem specificaly in how to identify human’s personality by reading of handwriting patterns. Therefore, technology of image processing, artificial neuron network, and hamming code hopefully can provide accurancy approach in order to find out any similiarity between test pattern and database pattern. Then, as the result computer is able to recognize and represent patterns of handwriting. Keywords: handwriting patterns, technology of image processing, artificial neuron network, hamming code